Profesionalisme Hakim Wanita di Pengadilan Agama Sungguminasa Kelas I B - Widia, Widia Amelia; Achmad Musyahid,; La Ode Ismail, (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2022)
This study aims to determine the professionalism of female judges in the Sungguminasa religious court as a requirement for female judges in implementing decisions with the values of responsibility as a fair court. This research is a qualitative study with a socio-legal research approach. The main data source of this research is interviews with female judges.Furthermore, data collection in this study uses observation, interviews and documentation.Meanwhile, data processing and analysis techniques are carried out through three stages, namely data reduction, data presentation and conclusion drawing.The results showed that the professionalism of female judges will show how the quality of decisions, so that female judges in the Sungguminasa religious court must be intellectual, experienced, responsible for legal and moral aspects and driven by the effectiveness of the caseload. Although female judges at the Sungguminasa religious court have good competence in terms of education, the lack of appealed decisions and their average experience of 15 years. However, it was found that there are several problems of female judges in maintaining their professionalism, including ineffective communication between judges and litigants, the existence of female judges' decisions that correlate with the woman solidarity, especially polygamy cases, there is still no time discipline, the imbalance in the ratio of the number of judges to the caseload will affect performance productivity because with the frequency of too many cases that must be tried by judges, it will affect the cognitive and emotional aspects of judges and support for increasing the professional capacity of judges has not been maximized. Moreover, in the age of technology, where judges must have competence in the IT field, it can be seen from the lack of opportunities to attend training or technical guidance. Moreover, in the age of technology, judges must have competence in IT. So it is necessary to attend training, especially senior judges.